小模数锥齿轮齿面质量检测及应用技术 - 李天兴; 邓效忠; 周广才; 孙银生 (Jixie chuandong)
In order to improve the application level of bevel gear tooth face inspection technology and effectively increase the processing precision and the meshing quality of the small module gear,the test and application of tooth surface accuracy and processing quality are analyzed based on one dimensional probe by means of the tooth surface structure characteristics and the measurement theory of small module bevel gear.Furthermore,the need for the tooth surface quality inspection in the digital manufacture of small module bevel gear was elaborated via the application methods of the measurement technique in the production practice.